Investigation on the Bending Mechanism of Single-Crystal Copper Under High Bending Rates via Molecular Dynamics - Peng Wu; Pengyue Zhao; Zhengkun Li; Jianwei Wu; Jiubin Tan (Micromachines)
Leaf spring-type flexible hinges serve as critical transmission components in kilogram quantization energy balance systems. Investigating their bending behavior is crucial for enhancing measurement accuracy and ensuring structural reliability. This work employs molecular dynamics simulations to analyze the mechanical properties and deformation characteristics of such hinges under varying bending rates. The findings reveal a significant correlation between the bending rate and the hinges’ plastic deformation and microstructural evolution, indicating the presence of a critical bending rate. When the bending rate is below the critical threshold, the hinges exhibit excellent structural stability, characterized by low dislocation density, reduced von Mises stress, and limited temperature rise, making them suitable for long-term use. Conversely, when the bending rate exceeds the critical threshold, the hinges undergo significant plastic deformation, including notable increases in stress and temperature concentration, as well as microstructural alterations. Specifically, the initially stable crystal structure is disrupted, leading to the formation of numerous defect structures. These changes result in localized instability and elevate the risk of fatigue damage. This work comprehensively elucidates the mechanical responses and failure mechanisms of flexible hinges, providing valuable data and guidance for their optimized design and application.